Effect of Intravenous Magnesium Sulfate on Improving the Quality of Anesthesia for Appendectomy Candidates under Regional Anesthesia - Mahzad Yousefian; Ali Mohammadian-Erdi; Afshan Sharghi; Mina Deldadeh Moghaddam (Journal of Ardabil University of Medical Sciences)
Background: One of the major challenges in surgery is pain control after surgery. The present study was conducted with the aim of investigating the role of magnesium sulfate in improving the quality of anesthesia in patients who are candidates for appendectomy surgery. Methods: In this clinical trial study, 42 people in the control group and 42 people in the intervention group were randomly included. For the intervention group, 50 mg/kg of magnesium sulfate was injected and for the control group, the same amount of distilled water was injected as a placebo. After surgery, the patients were examined for pain, nausea and vomiting, anxiety, blood pressure and heart rate, and the satisfaction of the surgeon in terms of muscle relaxation. Collected data were analyzed in SPSS-26 by statistical methods and p<0.05 was considered as significant level. Results: The average pain of the patients in the first, third, sixth and twelfth hours of the study in the intervention group with 1.4, 2.66, 3.3 and 3.19 were significantly lower than the control group. In terms of relaxation, a significant difference was observed between the two groups in the first, third, sixth, twelfth and eighteenth hours of the study. In the examination of nausea and vomiting of patients, no significant difference was observed between the two groups. During surgery, a significant difference was observed in patients receiving magnesium sulfate compared to the control group in terms of surgeon satisfaction. Conclusion: Magnesium sulfate was effective in controlling patients' pain and anxiety and surgeon's satisfaction during surgery, but it was not effective in controlling patients' nausea and vomiting.